1991
DOI: 10.1029/91ja00892
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐field current instability for substorm expansions

Abstract: We investigate a cross‐field current instability (CFCI) as a candidate for current disruption during substorm expansions. The numerical solution of the linear dispersion equation indicates that (1) the proposed instability can occur at the inner edge or the midsection of the neutral sheet just prior to the substorm expansion onset although the former environment is found more favorable at the same drift speed scaled to the ion thermal speed, (2) the computed growth time is comparable to the substorm onset time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
239
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 245 publications
(245 citation statements)
references
References 59 publications
5
239
1
Order By: Relevance
“…These events are referred to as current disruption, and a current-driven instability, known as the crossfield current instability (CCI), has been proposed to account for the observed current disruption features. Linear and quasi-linear calculations of CCI have yielded instability characteristics consistent with observed current disruption and substorm onset characteristics [Lui et al, 1991Yoon and Lui, 1993]. However, the CCI theory has not addressed at length how the instability onset location is tied to field lines threading an auroral arc except for noting that CCI occurs in regions where ions are unmagnetized, which in turn corresponds to a region of isotropic ion precipitation in the ionosphere.…”
Section: Introductionmentioning
confidence: 98%
“…These events are referred to as current disruption, and a current-driven instability, known as the crossfield current instability (CCI), has been proposed to account for the observed current disruption features. Linear and quasi-linear calculations of CCI have yielded instability characteristics consistent with observed current disruption and substorm onset characteristics [Lui et al, 1991Yoon and Lui, 1993]. However, the CCI theory has not addressed at length how the instability onset location is tied to field lines threading an auroral arc except for noting that CCI occurs in regions where ions are unmagnetized, which in turn corresponds to a region of isotropic ion precipitation in the ionosphere.…”
Section: Introductionmentioning
confidence: 98%
“…Their analysis assumed unmagnetized ions, so that an ion trajectory was treated as a straight line. One of the first applications of this instability was in the study of current disruption during substorm expansions in the geomagnetic tail (Lui et al 1991). Wu et al (1992) subsequently studied the instability more generally, and found that, even when relaxing the condition of unmagnetized ions and small β i , the zero-frequency instability persists, and in contrast to other cross-field drift instabilities (such as the modified two-stream instability), the growth rate remains high even for high β i .…”
Section: Appendix a Ion Weibel Instabilitymentioning
confidence: 99%
“…From this viewpoint, the diffusion is due to anomalous resistivity that waxes and wanes in response to the excitation and quenching of a current-driven instability; one that is excited when the current density gets above a critical level [Papadopoulos, 1985;Lui et al, 1991Lui et al, , 1993Yoon and Lui, 1996] and is quenched when the current density is driven below a level that is lower than the critical one.…”
Section: Lu Modelmentioning
confidence: 99%